2003
DOI: 10.1177/0145445503256316
|View full text |Cite
|
Sign up to set email alerts
|

The Conditioning of Dyspneic Suffocation Fear

Abstract: Previous studies in our laboratory have shown that a single exposure to 100% carbon dioxide (CO2) can serve as an effective unconditioned stimulus (US) in a Pavlovian aversive-context conditioning paradigm in rats. Although the US exposure parameters employed in the initial studies were sufficient for producing a context-specific enhancement of behavioral freezing and analgesia, it had yet to be determined whether variations of these CO2 conditioning procedures would produce other conditioning effects. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Freezing (an established measure of fear and panic-like behavior in rodents (8; 32)) was used to evaluate behavioral responses to CO 2 in TDAG8 +/+ /TDAG8 −/− mice. Following a CO 2 dose-response challenge, freezing was reduced in TDAG8 −/− mice relative to TDAG8 +/+ littermates on day 1 (Fig 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freezing (an established measure of fear and panic-like behavior in rodents (8; 32)) was used to evaluate behavioral responses to CO 2 in TDAG8 +/+ /TDAG8 −/− mice. Following a CO 2 dose-response challenge, freezing was reduced in TDAG8 −/− mice relative to TDAG8 +/+ littermates on day 1 (Fig 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Rising CO 2 concentrations lead to acidosis, creating a state of homeostatic imbalance resulting in defensive behavioral responses (6; 8; 32). CO 2 -evoked freezing is not completely attenuated in TDAG8 −/− mice, suggesting additional acid sensors (such as the acid-sensing ion channel 1 (ASIC1) in the amygdala (8) or acid sensing 5-HT neurons in the periaqueductal grey (36)) may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent behavioral response evoked by CO 2 was immobility (freezing-like behavior), that was markedly different between strains. Previous reports of CO 2 inhalation in rats have reported freezing behavior using a similar concentration (Mongeluzi et al, 2003). 10% CO 2 also evokes freezing in mice as reported by our group (Vollmer et al, 2016), and others (Ziemann et al, 2009; Taugher et al, 2014, Liebold et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…No comparison studies exist that have reported strain differences in CO 2 -evoked behavior. Previous studies have used SD or W rats in CO 2 inhalation paradigms (Mongeluzi et al, 2003; Dumont et al, 2010; Johnson et al, 2012; Schimitel et al, 2012). In agreement with our data, CO 2 inhalation (13%) did not affect immobility in Wistar rats (Schimitel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation